Effects of age at school entry (ASE) on the development of non-cognitive skills: Evidence from psychometric data - Andrea M. Mühlenweg; Dorothea Blomeyer; Manfred Laucht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2011)
We identify effects of age at school entry (ASE) on the development of child temperament. Our analysis is based on psychometric measures from a longitudinal cohort study of children in the Rhine-Neckar region in central Germany. In children with a higher ASE due to a birthday late in the year, we find more favorable outcomes with respect to several temperamental dimensions: These children are more persistent and less often hyperactive. The findings are robust if we control for the respective temperamental dimension before entering school. We also show that the ASE effect on persistence is stable over time by comparing the children at age eight and age eleven, after the children have entered Germany's segregated secondary-school tracks. At age eleven, we additionally find significant ASE effects on adaptability to change. Overall, the results point to a high degree of malleability in the considered non-cognitive skills after school entrance.
urn:nbn:de:bsz:180-madoc-31453
Keywords: I21; I28; J24; 330; Education; identification; instrumental variables; age at school entry (ASE)